Tinjauan Yuridis Pembatalan Perkawinan Atas Perkawinan Poligami Yang Tidak Memenuhi Syarat Di Indonesia - Wulandari, Septiayu Restu; Nurani, Sifa Mulya; Firdaus, Heldy (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2023)
Marriage is a legal and spiritual bond between a man and a woman with the aim of forming a happy and eternal family based on Belief in the One and Only God. Marriage is also said to be valid if it is carried out in accordance with religion and is registered according to applicable laws and regulations. In Indonesia, marriage is not only based on religious provisions but customs and traditions with the aim of having children. There are many cases in Indonesia that result in polygamous marriages. Polygamy has been regulated in such a way and in detail in Law Number 1 of 1974 concerning Marriage. The implementation of polygamy can only be carried out by submitting an application to the local court and even then for the reasons regulated by law and with the consent of the wife as the main requirement in a polygamous marriage. As for polygamous marriages that do not get the wife's approval, the marriage can be canceled because it does not meet the requirements for a polygamous marriage.